REDESAIN BANGUNAN INDUSTRI PAVING BLOCK DI DESA BUATA DENGAN PENDEKATAN ARSITEKTUR MINIMALIS - Andar, Muh.; A. Kiay Demak, Nini; Bakhtiar (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
This study aims to redesign the paving block industrial building in Buata Village by applying a minimalist architectural approach. The development of the paving block industry sector in an area is very important to support the needs of building materials. This research aims to redesign the paving block industry building using a minimalist architectural approach, this research was conducted from August to November 2023 at CV Shohat in Buata Village, Botupingee District, Bone Bolanggo Regency. This research method uses data collection and discussion methods, as well as the design process and design strategy. The results of this research show that the redesign of the paving block building in Gorontalo is needed to support the economic sector of the local community in order to meet the needs of community activities to compete with other regions in entering the paving block production industry.